Selective doping for bond relaxation towards enhanced structural reversibility in Ni-rich layered cathodes. (June 2022) - Luo, J.C.; Luo, J.F.; Chen, C.-L.; Huang, W.-H.; Chang, C.-K.; Chuang, Y.-C.; Zhang, J.L.; Zhao, R.R.
Abstract: Despite the high efficiency of trace dopants for better performance in layered cathodes, the structural origin of such improvement, beyond a simple replacement at the specific crystallographic site, has been rarely explored. Here we present comprehensive characterizations and analyses of structural modulations associated with trace amounts of Zr dopants in LiNi0·9 Co0·1 O2 using synchrotron X-ray diffraction and X-ray absorption spectra, together with electrochemical techniques. The Zr 4+ dopant preferentially replaces the Co 3+ at the Ni/Co (3 a ) site and has a limited effect on the Ni/Li mixing. Rather than the expected compression on neighbouring octahedra, the larger Zr 4+ leads to the relaxation of Ni–O bonds and thus reduces the Jahn-Teller effect and charge excitation. The local structure of the inactive Zr also relaxes to alleviate the distortion of octahedral Ni during cycling for extended durability. This work reveals the critical role of bond relaxation and illustrates how cationic dopants tune them via structural modulations, enabling excellent electrochemical performance for an efficient method to develop high-performance layered cathodes. Graphical abstract: Image 1 Highlights: Structural modulations associated with trace amounts of Zr dopants were studied. The Zr 4+ dopant preferentially replaces the Co at the Ni/Co (3 a ) site. The larger Zr 4+ leads to the relaxation of Ni-O bonds and thus reduces the Jahn-Teller effect and charge excitation. The critical role of Ni-O bonds via structural modulations were illustrated.